São Benedito e a Estação das Curas: saúde, devoção e constituições do território sul-mineiro - Pereira, Gabriela Acerbi (Universidade Federal de São Carlos, 2024)
The thesis addresses family experiences of devotion in São Benedito and in the Pretos Velhos entities in the south of Minas Gerais, considering the connections between both sacred presences in the territory. Based on these experiences of devotion, we investigated how generational health maintenance practices not only affected the organization and maintenance of families from a spiritual point of view, the perpetuation of traditional festivities linked to saints or consultation with entities, but the historical constitution of the South of Minas Gerais itself, relating them to understandings about healing, care and faith. Considering spiritual actions in the context of family trajectories, perceptions and ways of doing things inherited from ancestors were articulated and recorded, and to what extent these ways can narrate the historical transformations of the city of Poços de Caldas and its surrounding areas where it was dismembered between the 18th and 19th centuries, such as the municipality of Caldas. Based on 1) the lived narratives and memories shared by devout families, 2) together with the photographic collections of each family nucleus, 3) the consultation of archival documentation associated with the Festivals for São Benedito and Nossa Senhora do Rosário in the 19th century and the enslaved population in the territory, 4) as well as a bibliographic review about the slavery structure and the post-abolition context in the southern region of Minas Gerais, previous and current devotional experiences are described and analyzed. In this direction, the fieldwork develops from the cures experienced connected to ancestors (family members and Pretos Velhos entities) and which also situate São Benedito as a doctor for the population. All these processes were also considered to be situated in a region that was named Healing Station at the turn of the 19th century to the 20th century due to the presence of thermal waters and which, due to this factor, experienced high institutional investments from the empire, erasure policies aimed at the black population and indigenous people of the territory and a modernization project based on the logic of whitening and urban development associated with scientific thermalism and tourist exploitation of the region in such periods.
São Benedito and the Healing Station: health, devotion and constitutions of the southern territory of Minas Gerais
Keywords: São Benedito; Curas; Saúde; Território; Antepassados; Sul de Minas Gerais; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA DAS POPULACOES AFRO-BRASILEIRAS